Pilot prescription survey of antineoplastic agents: real‐world data from veterinary teaching hospitals in Japan. Issue 3 (17th May 2019) - Tanaka, Noriko; Takizawa, Tsuyoshi; Tanaka, Ryo; Okano, Shozo; Funayama, Shinji; Iwasaki, Toshio
Abstract: The collection of real clinical records from veterinary practices and analysis of these records helps to establish evidence‐based veterinary medicine and further improves animal health and welfare. Prior to the collection of nationwide clinical records, we downloaded the data from the digital accounting systems of two veterinary teaching hospitals in Japan, and the prescriptions of antineoplastic agents were surveyed for a 5‐year period from 2009 to 2013. The ratio of the number of patients prescribed antineoplastic agents to the total number of prescriptions was <5% at both hospitals, and >80% of those patients were dogs. The overall number of prescriptions included more oral rather than injectable formations, whereas among antineoplastic agents, injectable formulations were prescribed more frequently at both hospitals. The most frequently prescribed agents were almost identical at both hospitals: platinum compounds, such as carboplatin and cisplatin (CDDP), vincristine and doxorubicin. The most frequently prescribed product combined with CDDP was doxorubicin at Hospital A. Antiemetic agents combined with CDDP included dexamethasone, ondansetron and metoclopramide, but these antiemetic agents were combined fewer than 10 times among 197 CDDP prescriptions. The prescription history, including the number of prescriptions, dosing intervals and combined medications, was provided by the survey. Although the present database consisted of data from two hospitals, our results indicate that a broad analysis can be conducted using integrated data from multiple hospitals and practices for further cohort studies. Abstract : The digital health records from hospital systems were stored as database and the tendency of use of antineoplastic agents can be elucidated. The use of combined agents can be clarified. If digital health records can be stored as database, the cohort study of combination therapies can be conducted in veterinary medicine and review standard therapy protocols.